Kewirausahaan dan aspek-aspek studi kelayakan usaha / Gede Adi Yuniarta, Ni Luh Gede Erni Sulindawati, I Gusti Ayu Purnamawati. - GEDE ADI YUNIARTA; Ni Luh Gede Erni Sulindawati (Graha Ilmu, 2015)
ix, 118 hlm. ; 26 cm